OPTIMALISASI PEMBINAAN GURU BARU DALAM PEMBELAJARAN SEJARAH - Akhmad Arif Musadad (PAEDAGOGIA, 2008)
The problem that rose in this research is the teaching ability of new teacherswhich is relatively low. It was shown from: (1) teachers had less ability to make teachingpreparation; (2) teachers had less ability to perform the teaching procedure; (3) teachershad less ability to establish an interpersonal relation harmonically at classroom. Thisresearch is intended to solve the above problems. This research was applied on class 11.4SMU Negeri I Surakarta. The research was a collaborative research which involved seniorteachers of history subject matter and new teachers. Their active involvement in theresearch was enable them to broaden their roles by conducting self-reflection criticallytoward what they did in the class; and based on that reflection, their performance wasimproved. In line with the characteristics of the classroom research, the problem aboveshould be overcome by taking action in the form of directing new teachers. This is basedon the observation result and the interview that the low ability to teaching not only comesfrom the teachers themselves, but also from the less effective supervision. The researchresult shows that after carrying out the actions, the teaching ability has increasedsignificantly, in the turn it brings about a positive effect to the students learning activities.